(untitled) (GAIMS Journal of Medical Sciences, 2024)
The integration of structured mentoring programs within the medical curriculum and the inclusion of mentoring sessions in faculty development programs represent a forward-thinking approach by the NMC. These steps acknowledge the profound impact that effective mentoring can have on the professional and personal growth of medical students and the overall quality of healthcare delivery. By empowering faculty to become effective mentors, we can create a nurturing educational ecosystem that not only imparts knowledge but also fosters the holistic development of future doctors. This, ultimately, is a stride toward enhancing the quality of healthcare in India.